STUDY ON DIVERSITY OF ANAEROBIC Fe(II)-OXIDIZING, NO3-REDUCING BACTERIA IN SOME ECOLOGICAL ENVIRONMENTS IN VIETNAM - Tuyền, Nguyễn Thị; Hằng, Đinh Thúy (Vietnam Journal of Biotechnology, 2011)
Fe(II)-oxydiziag, NOs'-reducing bacteria in sediment samples collected from freshwater aquifer, flooded paddy soil and estuarine area were quantified and analysed on species composition. The MPN results showed that among the three studied environments, flooded paddy soil had the highest number of these bacteria (9.3 • 10^-g~'), five and two times higher than that of freshwater aquifer and estuarine sediment, respectively. Based on distinguish colony characteristics, 12 sfrains of Fe(II)-oxidizing, 'HOfreduing bacteria were isolated from MPN series and were set into five genetically different groups as proposed by ARDRA analyses with two restricition enzymes Haelll and Mspl, showing relatively high diversity of this bacterial group in the studied environments. Analysing species composition in the communities developed in MPN tubes at the highest dilution via PCR-DGGE of 16S rDNA revealed that Anaeromyxobacter species presented in all three above environments. In combination with the culturedependent studies, it was revealed that Paracoccus and Pseudomonas were dominant groups playing important roles in freshwater aquifer and flooded paddy soil, respectively. Sequencing of 16S rDNA from three representative strains IN2, IN7 and IN 12 suggested that they are respectively belonged to Anaeromyxobacter, Pseudomonas and Paracoccus genera.